Człowiek w dobie mediów - media w dobie biotechnologii - Chyła, Wojciech (Er(r)go. Teoria - Literatura - Kultura, 2002)
Wojciech Chyła - Man in the Age of Media – Media in the Age of Biotechnology The Author, by placing the media in a broader context of the biotechnological paradigm discusses natural environment, culture and ethics.